Masked prey - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Lucas Davenport novel., 2020)
The daughter of a U.S. Senator is monitoring her social media presence when she finds a picture of herself on a strange blog. She finds pictures of the children of other influential Washington politicians, walking or standing outside their schools, each identified by name. Surrounding the photos are texts of vicious political rants from a motley variety of radical groups. Is there an unstable extremist tracking the loved ones of powerful politicians with deadly intent? The FBI can't pin down the photographer's IP address, and no crime has actually been committed-- yet. The politicians call in someone who can operate outside the FBI's constraints: Lucas Davenport. -- adapted from jacket